Методологічне обґрунтування дослідження та розв'язання проблеми надійності функціонування транспортних систем - Аулін, В. В.; Голуб, Д. В.; Гриньків, А. В.; Лисенко, С. В. (ХНТУСГ, 2017)
В роботі дано методологічне обгрунтування дослідження та розв’язання про-блеми забезпечення та підвищення надійності функціонування транспортних систем на основі системно-спрямованого і фізико-інформаційного підходів. Розроблено схему ро-звитку методології досліджень, дано структуру теоретичних основ надійності транс-портних систем і процесів побудови методології фізико-інформаційного підходу. Побу-довано узагальнену схему і модель надійності функціонування транспортних систем. The current state of affairs in assessing and ensuring the reliability of freight and passenger transport by road significantly complicates the achievement of the transport sys-tem indicators of the transport strategy indicated in the Transport Strategy. At present, the quality indicator in transport proposed by scientists is reliability, taking into account, ba-sically, only the reliability of technical means, while the reliability of performed services is practically not considered. Also, there is no standardization of reliability in road transport and in the reports of motor transport enterprises there are no criteria that characterize the reliability and efficiency of their work. This is one of the reasons for the loss of road transport an important competitive advantage in the global market for the transportation of goods and passengers, as well as within the country in relation to other modes of transport. The methodological substantiation of the research and solution of the problem of providing and improving the reliability of transport systems functioning on the basis of system-directed and physical-information approaches is given in the work. The scheme of development of the research methodology has been developed, the structure of theoretical foundations of the reliability of transport systems and processes of construction of the meth-odology of the physico-informational approach is given. A generalized scheme and model of reliability of functioning of transport systems are constructed. The basic provisions fo-cused on the generalized scheme of research of the problem of maintenance and increase of reliability and efficiency of their functioning are developed.
Methodological justification of research and solution of the problem of reliability of transport systems functioning
Keywords: транспортна система; надійність; дослідження; системно-спрямований і фізико-інформаційний підхід; методологія; математична модель; transport system; reliability; research; system-oriented and physical-information approach; methodology; mathematical model